Network neutrality regulation: The fallacies of regulatory market splits - Günter Knieps; Volker Stocker (Intereconomics, 2015)
Network neutrality regulations for the Internet have been discussed for about a decade. In Europe recent efforts have produced a proposal by the European Commission that envisages the introduction of a two-tiered Internet traffic regulation based on a regulatory market split between the markets for 'public' Internet traffic services and the markets for specialised services offering higher and ensured quality of data transmission. We argue that regulatory market splits are artificial and the proposed regulation of markets for Internet traffic services constitutes a regulatory fallacy.
Keywords: 330; Internet; Internetnutzung; Telekommunikationsnetz; Netzregulierung; EU-Staaten